A multi-purpose Gripper for KUKA KR-60 welding robot and inspection chamber - Escalante, Wilmer (2023)
At present, imperfections are still observed in the welding of the vehicle chassis, due to the fact that the inspection of the welding seam is still carried out manually. In other words, there are still companies that depend on an operator to verify the welding, which has resulted in less durability of the vehicle chassis, as they do not have adequate reinforcement when entering areas where greater strength and traction is required. For this reason, the use of a gripper is proposed, the purpose of which will be to carry out and inspect the weld seam. This mechanism consists of the use of 3 tools: MIG torch, dremel and camera, each tool will be used in a certain period of time independently in order to guarantee the correct welding seam. For this purpose, the analysis of the behaviour of the robotic arm will be taken into consideration by using the Denavit Hartenberg algorithm, which helps us to establish the reference systems for each link of the robot. Firstly, MIG welding is used. Secondly, we wait for a short period of time to let the weld bead cool down, then we use the dremel tool with a twisted conical brush accessory to perform a little reaming to remove some surface impurities. Finally, after waiting a short period of time for the effect to take effect, a Logitech c922 camera is used to capture an image of the bead and perform image processing to see what type of imperfection the weld has. The design uses duraluminium, MDF, zinc-plated rods and ABS filament for the 3D printer. The expected result is to obtain a correct quality control of the welding to guarantee the durability of the fundamental part of the vehicle.